2017
DOI: 10.1096/fj.201700398r
|View full text |Cite
|
Sign up to set email alerts
|

A 2A adenosine receptors control pancreatic dysfunction in high‐fat‐diet‐induced obesity

Abstract: Adenosine, a key extracellular signaling mediator, regulates several aspects of metabolism by activating 4 G-protein-coupled receptors, the A, A, A, and A adenosine receptors (ARs). The role of AARs in regulating high-fat-diet (HFD)-induced metabolic derangements is unknown. To evaluate the role of AARs in regulating glucose and insulin homeostasis in obesity, we fed AAR-knockout (KO) and control mice an HFD for 16 wk to initiate HFD-induced metabolic disorder. We found that genetic deletion of AARs caused imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 68 publications
0
23
1
Order By: Relevance
“…A2aAR KO mice had greater abdominal fat mass, increased adipocyte size than WT mice, greater insulin resistance and glucose intolerance [ 79 , 80 ]. Furthermore, in another study, A2aAR KO mice fed an HFD for 16 weeks had reduced glucose tolerance due to a decrease in insulin secretion by the pancreas rather than a difference in insulin sensitivity [ 81 ]. In an HFD model of obesity in Swiss mice, the administration of CGS21680, an A2aAR agonist, improved glucose homeostasis, as determined by insulin tolerance test, and reduced inflammatory markers such as tumor necrosis factor alpha (TNFα) systemically and in the visceral adipose tissue [ 82 ].…”
Section: Adenosine Receptors In Glucose Homeostasis and Obesitymentioning
confidence: 99%
“…A2aAR KO mice had greater abdominal fat mass, increased adipocyte size than WT mice, greater insulin resistance and glucose intolerance [ 79 , 80 ]. Furthermore, in another study, A2aAR KO mice fed an HFD for 16 weeks had reduced glucose tolerance due to a decrease in insulin secretion by the pancreas rather than a difference in insulin sensitivity [ 81 ]. In an HFD model of obesity in Swiss mice, the administration of CGS21680, an A2aAR agonist, improved glucose homeostasis, as determined by insulin tolerance test, and reduced inflammatory markers such as tumor necrosis factor alpha (TNFα) systemically and in the visceral adipose tissue [ 82 ].…”
Section: Adenosine Receptors In Glucose Homeostasis and Obesitymentioning
confidence: 99%
“…During chronic inflammation, a common factor in metabolic syndromes, the local hypoxic microenvironment may upregulate extracellular adenosine production. Adenosine controls insulin signals in adipose tissue, muscle, and liver [ 30 , 31 ], and all four adenosine receptors are reportedly involved in glucose homeostasis, adipogenesis, and insulin resistance [ 32 ]. Increased levels of IDO-generated tryptophan metabolites, the kynurenines, may promote metabolic syndrome development via pro-oxidative, neurotoxic, and apoptotic activities, along with upregulation of inducible nitric oxide synthase, phospholipase A2, arachidonic acid, prostaglandin, 5-lipoxygenase, and leukotriene cascade [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated that A 2A receptor knockout mice exhibit impaired thermogenesis, oxygen consumption, and lipolysis [20]. Moreover, Csóka et al, (2017) observed the reduced food intake in such mice and consequently a lower body mass as compared to control animals [21]. A strong functional interaction between the dopamine D 2 and adenosine A 2A receptors [22] has been further discovered and a blockade of adenosine A 2A receptor can even mimic the action of D 2 agonists [23].…”
Section: Introductionmentioning
confidence: 99%